Perkembangan Dewasa Madya Sebuah Studi Kasus - Ferdyansyah, Muhammad; Masfufah, Ulfa (Universitas Negeri Malang, 2022)
Abstract: Middle adulthood or what is also called middle age in chronological terminology, which generally ranges from 40-60 years of age. The purpose of this study was to determine the development of the author's parents in the middle adulthood phase from the physical, cognitive, socio-emotional aspects, the concept of wisdom as well as self-reflection for researchers and readers. The method used in this study is observation and interviews. This research is a qualitative descriptive research. After conducting the research, data were obtained in the form of changes in physical, cognitive, socio-emotional, and the concept of wisdom in the middle adulthood phase. There are many factors that affect the growth and development of a person. Internal and external factors in a person's development are interrelated and cannot be separated Abstrak: Masa dewasa madya atau yang disebut juga usia setengah baya dalam usia kronologis yaitu antara usia 40 - 60 tahun. Tujuan dari penelitian ini adalah untuk mengetahui perkembangan orangtua pada fase dewasa madya dari aspek fisik, kognitif, sosioemosi, dan konsep kearifan menurut subjek. Metode yang digunakan dalam penelitian ini adalah observasi dan wawancara. Penelitian ini adalah penelitian deskriptif kualitatif. Hasil dari penelitian, diperoleh data berupa terjadi perubahan fisik, kognitif, sosioemosional, dan konsep kearifan pada fase dewasa madya. Terdapat banyak faktor yang mempengaruhi tumbuh kembang seseorang. Faktor internal dan eksternal dalam perkembangan seseorang saling berkaitan dan tidak dapat dipisahkan.